Anti-staphylococcal activity of Syagrus coronata essential oil: Biofilm eradication and in vivo action on Galleria mellonela infection model. (June 2019) - Souza dos Santos, Bruno; Bezerra Filho, Clóvis Macedo; Alves do Nascimento Junior, José Adelson; Brust, Flávia Roberta; Bezerra-Silva, Patrícia Cristina; Lino da Rocha, Suyana Karoline; Krogfelt, Karen Angeliki; Maria do Amaral Ferraz Navarro, Daniela; Tereza dos Santos Correia, Maria; Napoleão, Thiago Henrique; Nascimento da Silva, Luís Claudio; Macedo, Alexandre José; et al.
Abstract: In this study, essential oil extracted from Syagrus coronata seeds (SCEO) was evaluated for antibacterial and antibiofilm activities against Staphylococcus aureus ; in addition, Galleria mellonella model was used as an in vivo infection model. SCEO was mainly composed by fatty acids (89.79%) and sesquiterpenes (8.5%). The major components were octanoic acid, dodecanoic acid, decanoic acid and γ-eudesmol. SCEO showed bactericidal activity (minimal bactericidal concentration from 312 to 1250 μg/mL) against all tested S. aureus clinical isolates, which showed distinct biofilm-forming and multiple drug resistance phenotypes. SCEO weakly reduced biomass but remarkably decreased cell viability in pre-formed biofilms of S. aureus isolate UFPEDA-02 (ATCC-6538). Electron microscopy analysis showed that SCEO treatments decreased the number of bacterial cells (causing structural alterations) and lead to loss of the roughness in the multiple layers of the three-dimensional biofilm structure. In addition, overproduction of exopolymeric matrix was observed. SCEO at 31.2 mg/kg improved the survival of G. mellonela larvae inoculated with UFPEDA-02 isolate and reduced the bacterial load in hemolymph and melanization. In conclusion, SCEO is an antibacterial agent against S. aureus strains with different resistance phenotypes and able to disturb biofilm architecture. Our results show SCEO as a potential candidate to drug development. Highlights: Essential oil extracted from Syagrus coronata seeds (SCEO) was obtained. SCEO showed bactericidal activity (MBC from 312 to 1250 μg/mL) against S. aureus. SCEO decreased cell viability in pre-formed biofilms of S. aureus isolate. SCEO improved the survival of G. mellonela larvae inoculated with S. aureus.